Resilience in maternal, newborn, and child health in low- and middle-income countries: findings from a scoping review - Olusesan Ayodeji Makinde; Babasola O. Okusanya; Nchelem K. Ichegbo; Ifeanyi C. Mgbachi; Emmanuel Olamijuwon; Fatima Abdulaziz Sule; Olalekan A. Uthman (Reproductive Health)
Abstract Objectives The research objectives were to identify and synthesise prevailing definitions and indices of resilience in maternal, newborn, and child health (MNCH) and propose a harmonised definition of resilience in MNCH research and health programmes in low- and middle-income countries (LMICs). Design Scoping review using Arksey and O’Malley’s framework and a Delphi survey for consensus building. Participants Mothers, new-borns, and children living in low- and middle-income countries were selected as participants. Outcomes Resilience as defined by the authors was deduced from the studies. Results Twenty-two out of 76,566 cited studies published between 2006 and 2010 were included in the review. Thirteen (59.1%) examined maternal resilience, and nine (40.9%) examined newborn and child health resilience; most of the included studies were quantitative (n = 17; 81%). Seven studies defined ‘resilience’ in the context of maternal health, most of which described the term at the individual level. ‘Maternal resilience’ was measured using validated scales in five studies; another five defined newborn and child resilience. Only one reviewed study used maternal characteristics to identify newborn and child resilience. The synthesised consensus definition of ‘maternal, newborn, and child resilience’ is ‘A woman’s ability to prevent or adapt to significant and challenging circumstances including threats, tragedy, and trauma to herself during pregnancy, childbirth, and puerperium and to her neonates or children five years or younger’. Conclusion The information identified was limited but included a few definitions of resilience in MNCH and an index of child resilience in LMICs. The proposed definition is useful for MNCH programme implementation and interventions in LMICs. Scoping review registration: The protocol for this review was registered in the open science framework at the registered address ( https://osf.io/jt6nr ).